THE INFLUENCE OF POWER RELATIONS WHICH GIVE RISE TO GENDER INEQUALITY ON THE MAIN CHARACTER IN THE NOVEL THE RED QUEEN BY PHILIPPA GREGORY - Rustiyani Rustiyani; Agnes Setyowati H; Ni Made Widisanti S. (Universitas Pakuan, 2019)
ABSTRACT The topic of this research is the influence of power relations which gave rise to injustice against the female character in Philippa Gregorys The Red Queen. In a relationship, whether between individuals or groups, there is usually a figure who has more control than others. In this sphere, Foucault calls this kind of relationship power relationsâ€. Power relation is something that can be said to be commonplace, but this is detrimental to one party, especially to women. Therefore, this study aims to show the harm suffered by women due to the influence of power relations by centralizing the analysis on Lady Margaret Beaufort, the main character of a noble woman in the context of the 14th and 15th centuries in England. The type of research used is qualitative research that is supported by library technique. The research findings shows that power relations in the 14th and 15th centuries are very strong in the life of the royal community, and it gives birth of injustice to the main character such as: (1)Steriotype, (2)Subordination, (3)Symbolic violence and, (4)Marginalization. Keywords: Power Relations, Woman, Main Character, Injustice